Vacant Manganese‐Based Perovskite Fluorides@Reduced Graphene Oxides for Na‐Ion Storage with Pseudocapacitive Conversion/Insertion Dual Mechanisms. Issue 38 (26th May 2021) - Huang, Yongfa; Ding, Rui; Ying, Danfeng; Yan, Tong; Huang, Yuxi; Tan, Caini; Sun, Xiujuan; Gao, Ping; Liu, Enhui
Abstract: Na‐ion capacitors (NICs) and Na‐based dual‐ion batteries (Na‐DIBs) have been considered to be promising alternatives to traditional lithium‐ion batteries (LIBs) because of the abundance and low cost of the Na‐ion, but their energy density, power density and life cycle are limited. Herein, dual‐vacancy (including K + and F − vacancies) perovskite fluoride K0.86 MnF2.69 @reduced graphene oxide (rGO; recorded as Mn−G) as anode for NICs and Na‐DIBs has been developed. The special conversion/intercalation dual Na‐ion energy storage mechanism and pseudocapacitive dynamics are analyzed in detail. The Mn−G//AC NICs and Mn−G//KS6 Na‐DIBs delivered a maximum energy density of 92.7 and 187.6 W h kg −1, a maximum power density of 20.2 and 21.12 kW kg −1, and long cycle performance of 61.3 and 68.4 % after 1000 cycles at 5 A g −1, respectively. Moreover, Mn−G//AC NICs and Mn−G//KS6 Na‐DIBs can work well over a wide range of temperatures (−20 to 40 °C). These results make it competitive in Na‐ion storage applications with high energy/power density over a wide temperature range. Abstract : Some like it hot or cold : A novel dual‐vacancy manganese‐based perovskite fluoride@reduced graphene oxide (rGO) was synthesized in one‐pot, and its structure‐activity relationship was analyzed by physical characterization and electrochemical methods. Ex‐situ techniques were used to analyze the pseudo‐capacitance conversion/intercalation dual Na‐ion energy storage mechanisms. Finally, assembled Na‐ion capacitors and Na‐based dual‐ion batteries showed good electrochemical performance at high (40 °C) or low (−20 °C) temperature.